A Correction Method for Measuring Spectral Irradiance of Light Sources Based on Differential Quadrature Method. (1st June 2015) - Wang, Yanfei; Dai, Caihong; Wu, Zhifeng; Chen, Binhua
Abstract : A novel correction method was demonstrated for measuring spectral irradiance of light sources with a narrow bandwidth. Using the correction method based on differential quadrature method, an estimate of the true value was achieved with measured values of seven adjacent points. The formula of this correction method was derived. Numerical simulations and experimental validation of this correction method were also performed, respectively. This correction method could be used in radiometry, photometry, colorimetry, and other spectrometry fields, especially in the spectrum measurement of LED lamp.